Micronutrients: Speculation on Inborn Errors, Nutrigenomics, Evolution, the Microbiome, and Nutritional Immunity. (23rd March 2018) - Clayton, Peter T.; Mills, Philippa B.
Many micronutrients or cofactors derived from micronutrients are highly reactive, hence their role in catalysis of reactions by enzymes. The concentration of cofactors has to be kept low to avoid unwanted reactions while allowing them to bind to the (apo)enzymes that need them. A new disorder causing B6-responsive epilepsy (proline synthetase cotranscribed bacterial homologue deficiency) is probably due to the absence of an important intracellular pyridoxal phosphate chaperone. The availability of some micronutrients varies by orders of magnitude in different geographical areas. Selenium is both essential and toxic, and during evolution, different populations have had to adapt to this differing availability. An "inborn error of metabolism (IEM)" in a low selenium area of China may be a selective advantage in a high selenium area and vice versa; the concept of nutrigenomics is an important one for micronutrients. The gut flora may make an important contribution to vitamin synthesis. This is difficult to study, but experiments can be undertaken with the nematode, Caenorhabditis elegans (with or without an IEM) and a single clone of Escherichia coli (with or without an IEM) as food and gut flora. This model shows that the gut microbiome can have profound influences on the folate cycle and associated vitamins. Our innate immune system makes use of the micronutrient requirements of pathogens and can deprive a pathogen of essential micronutrient(s) or expose it to toxic levels. It is not surprising, therefore, that some mutations affecting the way the host handles micronutrients can confer an advantage in resistance to infection and this may have acted as a selective advantage during evolution. This will be discussed by reference to the relationship of inborn errors to resistance to malaria. Conversely, other inborn errors of micronutrient metabolism are likely to make it more difficult for the host to use nutritional immunity to fight infection; this probably accounts for the list of infections that are more serious in patients with hereditary haemochromatosis.